Integritas Perilaku Kepemimpinan Publik Walikota Bandung - Raykevin Bagus Julian Maramis (Otoritas: Jurnal Ilmu Pemerintahan, 2017)
Some of the achievements that Bandung City had today, is a positive value for the performance of Bandung City Government. Public leadership behavior of Bandung City Mayor becomes one of a several factors that increasing the performance of Bandung City Government. The purpose of this study is to discover the tendency of public leadership behaviours of Bandung City Mayor based on five dimensions namely: accountability leadership, lawfulness leadership, ethical leadership, political loyal leadership, dan network governance leadership. The method of this research is a quantitative descriptive study, by using data collection techniques such as questionnaires from 30 respondents and interviews. The results of this study shows that the tendency of public leadership behavior of the mayor of Bandung City is inclined to the lawfulness leadership with a good category . This evidence comes from the behavior of the public leadership of Bandung City Mayor which always emphasize every employee to always obey and properly follow the rules and regulations that has been established.